FACTORS THAT AFFECT THE MASINICAL PRODUCTIVITY IN THE INDONESIAN RAILWAY INDUSTRY - Soelton, Mochamad (Archives of Business Research, 2020)
This research aims to examine and analyze the effect of stress, psyches environment and self-efficacy on employee productivity with burnout as an intervening variable for employees of The Indonesia Railway Industry. The method used in this research is descriptive method. The object of this research is 43 employees of The Indonesia Railway Industry. The approach used in this research is the Component or Variance Based Structural Equation Model with the Smart-PLS analysis tool. The result showed stress that has positive and significant effect on burnout of The Indonesia Railway Industry. Psyches environment that has a negative and significant effect on burnout of The Indonesia Railway Industry. Self-efficacy that has a negative and significant effect on burnout of The Indonesia Railway Industry. Stress that has a negative and significant on productivity of The Indonesia Railway Industry. Psyches environment that has a positive and significant on productivity of The Indonesia Railway Industry. Self-efficacy that has positive and significant on productivity of The Indonesia Railway Industry. Burnout that has negative and significant effect on productivity of The Indonesia Railway Industry.